Parteilichkeit und Aufklärung: Zur Kritik der Mosaik-Linken - Neupert, Alexander (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2013)
The paper deals with the importance of common theoretical positions for cooperation between political forces. Intended is a critique on the idea that mere shared interests are a sufficient foundation for such efforts. Discrepancies between partial interests and a wider orientation are discussed in reference to Rosa Luxemburg and Anton Pannekoek.